2006
DOI: 10.1016/j.colsurfa.2005.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Sodium meta-autunite colloids: Synthesis, characterization, and stability

Abstract: Waste forms of U such as those in the United States Department of Energy's Hanford Site often contain high concentrations of Na and P. Low solubility sodium uranyl phosphates such as sodium meta-autunite have the potential to form mobile colloids that can facilitate transport of this radionuclide. In order to understand the geochemical behavior of uranyl phosphate colloids, we synthesized sodium meta-autunite colloids, and characterized their morphology, chemical composition, structure, dehydration, and surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…It is rather difficult to precipitate uranium as phosphate in the presence of excess carbonate at pH 9.0. However, earlier studies (29) have shown that it is feasible only at log(PO 4 Ϫ3 /CO 3 Ϫ2 ) values of ϾϪ3. We determined the amount of P i released by our strains in the absence of uranium and calculated the log(PO 4 Ϫ3 /CO 3 Ϫ2 ) value in assays containing 0.5 to 5 mM uranium concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…It is rather difficult to precipitate uranium as phosphate in the presence of excess carbonate at pH 9.0. However, earlier studies (29) have shown that it is feasible only at log(PO 4 Ϫ3 /CO 3 Ϫ2 ) values of ϾϪ3. We determined the amount of P i released by our strains in the absence of uranium and calculated the log(PO 4 Ϫ3 /CO 3 Ϫ2 ) value in assays containing 0.5 to 5 mM uranium concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Before uranium bioreduction could be stimulated during a pilot test study, however, groundwater had to be treated above ground to remove nitrate (a more favorable terminal electron acceptor), the pH adjusted to circumneutral values to promote the growth of iron-and sulfate-reducing bacteria (Finneran et al, 2002;Senko et al, 2002;Istok et al, 2004), while simultaneously removing aqueous aluminum and calcium to prevent formation of Al-hydroxide precipitates at pH > 4.5 and stable aqueous Ca-U-CO 3 complexes. U(VI) also forms highly insoluble phosphate minerals with a 1:1 stoichiometry in a wide range of pH (Ohnuki et al, 2004;Zheng et al, 2006;Wellman et al, 2007). These minerals comprise members of the autunite/meta-autunite group, including calcium autunite [Ca(UO 2 ) 2 (PO 4 ) 2 ], chernikovite [H 2 (UO 2 ) 2 (PO 4 ) 2 ], saléeite [Mg(UO 2 ) 2 (PO 4 ) 2 ], and ankoleite [K 2 (UO 2 ) 2 (PO 4 ) 2 ], and remain stable for long periods of time (Jerden and Sinha, 2003), suggesting that uranyl phosphates may provide a long-term sink for uranium in contaminated environments.…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of sodium autunite {(Na 2 ,Ca)[(UO 2 )(PO 4 )] 2 (H 2 O) 8 }, about 2.5×10 -7 molar at pH 4.5-8.5 (Zheng et al 2006), is lower than that of metaschoepite. The conversion of metaschoepite to sodium autunite can occur by the addition of sodium phosphate salts to the metaschoepite-bearing sludge and by providing, as required, a sufficient source of calcium.…”
Section: Test Series 32 and 33: Small Scale Warm Static Tests With mentioning
confidence: 99%